Muslim Communities Effort to Spread Moderated Islamic Values in England - Shiddieq, Mohammad Raffliy Asman Ash; Pradana, Hafid Adim (UNIDA Gontor, 2023)
This article focuses on showing how the efforts of Muslims in England are trying to fight the unreliable stigma and accusations of being a radical religion by spreading the values of moderate Islam that are peaceful without violence. This article is important and interesting because the willingness to fight the stigma is carried out in various fields and levels in the hope of gaining legitimacy from the British government. To understand the efforts to spread Islamic values in England, this study uses Martha Finnemore's theory of constructivism with descriptive analysis in order to better understand what the actions of the Muslim community are like. The data was collected using the Harzing Publish or Perish application through data sources from Google Scholar within the time range from 2005 to 2021, and the literature was categorised and analysed using the Nvivo 12 Plus application. The result is that the spread of moderate Islamic values started with Muslim individuals trying to separate extremism from Islam and then Muslim organisations trying an open approach and discussion towards non-Muslims until they got legitimacy. After that, the government builds an anti-extremism institute as a clear divider between peaceful Islam and radical Islam. This study contributes to explaining the deradicalization efforts of British Muslims in depth, which has not been explained in previous studies. This study is limited to only explaining how to deradicalize Islam in the domestic scope